SYNTHESIS OF FOOD GRADE SALT FROM BRINE WATER OF TIRTA SANITA BOGOR - Ermiziar Tarmizi; Kudrat Sunandar; Agam Duma Kalista Wibowo (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2021)
Tirta Sanita Bogor brine water contains high concentrations of sodium (Na). It also contains calcium (Ca) and magnesium (Mg). The purpose of this research is to make the food grade salt with relatively low Ca and Mg content. The process was carried out in two methods, the first method was chemical precipitation which was divided into two stages, the removal of the Mg element using a limestone compound (CaCO3) which has been calcined at 900ËšC for 6 hours, and the removal of Ca element using Li2CO3 compound. The second method was traditional evaporation which was conducted using prism greenhouse technology. The brine filtrate was reacted with Na2CO3 and the results were analyzed using the ICP-OES. The results showed that the NaCl content was 80% by the chemical precipitation and traditional evaporation methods.